Indications and Use of Hydrogen Peroxide during Microvascular Flap Reconstruction Surgery: A Literature and Procedural Use Review - Rodriguez-Collazo, E.; Riddle, D.; Schmidtke, K. (Journal of Reconstructive Microsurgery Open, 2017)
Microvascular flap reconstruction surgery is a limb preservation procedure performed in an effort to maintain the integrity of the lower limb and avoid amputations. Individuals facing the prospect of amputation often have long-term diabetes with multiple comorbidities, including severe peripheral vascular disease; peripheral arterial disease; chronic ulcerations; and Charcot arthropathy. Long-term clinical research has shown that these patients are at much higher risk for secondary amputations after a first amputation is performed. According to Sohn et al, Charcot and ulcer groups had 4.1 and 4.7 amputations per 100 person-years, respectively. In patients younger than 65 years old at the end of follow-up, amputation risk, relative to patients with Charcot alone, was 7 times higher for patients with ulcer alone and 12 times higher for patients with Charcot and ulcer. Patients with infected hardware, suffering from acute ulcerative conditions, may also be candidates for this type of surgery due to extensive tissue loss secondary to infection. Microvascular flap reconstruction surgery is a highly technical surgery involving the use of orthoplastic techniques, which is performed under ×3.5 loupe magnification. Due to the inability to perform this procedure with the use of a tourniquet, visibility within the field is obfuscated from continuous blood flow along the dissected muscle belly. Hydrogen peroxide (H2O2) is an excellent alternative to tourniquet use. The use of H2O2 allows additional benefits, such as visual field clearance and antisepsis.
Keywords: hydrogen peroxide; hemostasis; embolization